Uncertain chances science, skepticism, and belief in nineteenth-century American literature - Lee, Maurice S. (New York ; Oxford : Oxford University Press, 2012)
Maurice Lee's study illustrates how writers such as Poe Melville, Douglass, Thoreau, Dickinson, and others participated in a broad intellectual and cultural shift in which Americans increasingly learned to live with the threatening and wonderful possibilities of chance.
Includes bibliographical references and index.
Description based on print version record.
Keywords: American literature -- 19th century -- History and criticism; Chance in literature; Probability in literature; Skepticism in literature; Belief and doubt in literature; Pragmatism in literature; Literature and science -- United States -- History -- 19th century; Christianity and literature -- United States -- History -- 19th century; United States -- Intellectual life -- 19th century